El duelo de los inmigrantes (proyecto de intervención grupal) - Gamarra, Tomàs; Pérez, Noemí; Sala, Silvia; Codina, Belen; Torralba, Victoria; Carbonell Cutillas, María Carmen; Gonfaus, Marta (Acciones e Investigaciones Sociales, 2011)
El duelo de los inmigrantes (proyecto de intervención grupal)